PREPARATION AND CHARACTERIZATION PHISICOCHEMICAL PROPERTIES OF MULTI COMPONENT KETOPROFEN WITH CO-FORMER GLUTAMINE - Helen Sonita; Erizal Zaini; Salman Umar (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Ketoprofen is a non-steroidal anti-inflammatory compound (NSAID) which has low solubility in water. This study aimed to increase the dissolution rate of ketoprofen by forming multicomponent ketoprofen-glutamine in ratios of 1:1, 1:2, and 2:1 using the solid-state grinding method. The samples were characterized using Powder X-Ray Diffractometry (PXRD), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared (FTIR) Spectroscopy, Scanning Electron Microscope (SEM), solubility, dissolution rate, and stability tests. These results indicated the formation of a eutectic mixture of ketoprofen-glutamine. From the study of the ketoprofen–glutamine eutectic mixture, the eutectic point at a ratio of 1:1 was obtained at 95.51°C. The PXRD spectra did not show new crystal habits; the solubility test of the eutectic mixture of ketoprofen-glutamine showed increases of 2.450, 2.518, and 2.374 times, respectively. The eutectic mixture of ketoprofen–glutamine had rod-like crystal particles that formed and aggregated. The samples showed an increased dissolution rate of ketoprofen. The stability test showed that ketoprofen-glutamine was stable during storage at 75% relative humidity (RH) and 40 °C for 6 months; there was only a decrease in intensity, as seen from the PXRD spectrum. Keywords: eutectic mixture, ketoprofen, glutamine, solubility, dissolution rate, stability